ANALYSIS OF GARUT REGENCY STUDENTS' INTEREST IN RUNNING AND JUMPING ATHLETICS IN THE 2025 WEST JAVA STUDENT CHAMPIONSHIP - Asma Bara; Anne Patmah Annisa (PT Mediatama Zayna Indonesia, 2025)
Sports play a crucial role in shaping students’ physical, mental, and social development. Athletics, particularly running and jumping events, serve as a fundamental discipline and a benchmark of physical ability, as well as an integral part of the Physical Education, Sports, and Health (PJOK) curriculum. However, students’ interest in athletics often lags behind more popular sports. This study aims to analyze the level of interest among students from Garut Regency in athletics, specifically running and jumping events, during the 2025 West Java Student Athletics Championship. The research employed a quantitative approach with a descriptive method. The sample consisted of 54 students selected through purposive sampling based on participation in running and jumping events. The research instrument was a Likert-scale questionnaire with 20 items, tested for validity and reliability. Data were analyzed using descriptive statistics through frequency and percentage calculations. The findings revealed that the majority of students demonstrated a moderate level of interest (60%), followed by high (28%) and low (12%) categories. These results align with previous studies showing that students’ interest in athletics generally falls within moderate to high categories. The presence of students with high interest indicates potential for further development through structured training, adequate facilities, and sustainable competitions. In conclusion, while students in Garut Regency show a reasonably good level of interest in athletics, strengthening development strategies is essential to elevate moderate interest into high interest and to prepare potential young athletes for future achievements.